National allegories in third world novels - Sezer, Feride Evren. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2005., 2005)
This thesis focuses on the national allegorical aspects in Salman Rusdie’s Midnight’s Children and Nuriddin Farah’s Maps. Although allegorical elements are explored here, the thesis concerns itself with the identification problem of the third world individual, which amounts to the encounter between the West and the East through colonial and postcolonial experiences. The aim is to study how the individual reflects on him/herself with reference to his/her conception of the outside world, and how the two novels criticize and deconstruct fixed meanings imposed on the third world individual.
Keywords: Allegory.